Shifting the use of Leuit in agricultural systems - Ani Fathurohmah; Djoko Adi Prasetyo (Universitas Airlangga, 2020)
Leuit is a grain bin and has a function to store the community’s rice grains of Suka Puyuh Village. This research aims to describe the preservation effort of Leuit in Suka Puyuh Village. Leuit has been preserved through family trait, Leuit reactivation program, and exploiting ruwat lembur tradition as the mechanism. The villagers’ attempts to preserve the Leuit intrigued the researcher to conduct further research concerning the existence of the Leuit in Suka Puyuh Village. This research is an ethnographic research along with employing a descriptive method and qualitative approach. Further, the technique of data collection uses observation methods and depth interviews. The obtained data are analyzed using Wilbert E. Moore’s Social Change theory. The results of this study indicate that Leuit in Kampung Suka Puyu’s community life has undergone a shift because of the change of social structure. Development of the agricultural system from simple to a more advanced and varied level has an impact on the shift of farming system to gardening system.